(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of using RTR Cone bone graft material for alveolar ridge preservation following atraumatic tooth extraction at the Institute of Odonto-Stomatology, Hanoi Medical University, during the period 2020-2021. Methods: A cross-sectional descriptive study was conducted on 40 patients who underwent atraumatic tooth extraction at the Dental Center, 225 Truong Chinh, Institute of Odonto-Stomatology, Hanoi Medical University, from August 2020 to July 2021. The study variables included age, gender, and alveolar bone dimensions measured on Coronal, Axial, and Sagittal sections immediately after extraction and at 3 months postoperatively. Additional parameters included bone density, postoperative pain level, bleeding, and clinical outcomes at 3 and 7 days after surgery. Results: The mean age of the patients was 42.88 ± 10.86 years. In both the RTR graft group and the control group, alveolar bone dimensions at all measured sites (Coronal, Axial, and Sagittal sections) at 3 months were reduced compared to those measured immediately after extraction. After 3 months, bone density in both groups was predominantly classified as D3. All patients (100%) experienced pain only immediately after surgery, with mild pain accounting for the majority of cases. At 7 days post-extraction, 100% of patients in the intervention group were evaluated as having good clinical outcomes, whereas this proportion was 90% in the control group. Conclusion: The mean patient age was 42.88 ± 10.86 years. Alveolar bone dimensions across all three sections decreased at 3 months compared to the immediate post-extraction measurements. After 3 months, bone density in both groups was mainly classified as D3. All patients experienced only immediate postoperative pain, which was predominantly mild. At 7 days post-extraction, 100% of patients in the intervention group achieved good outcomes, compared to 90% in the control group.